2018
DOI: 10.1002/ijc.31935
|View full text |Cite
|
Sign up to set email alerts
|

Combined genetic and epigenetic alterations of the TERT promoter affect clinical and biological behavior of bladder cancer

Abstract: In urothelial bladder cancer (UBC), risk stratification remains an important unmet need. Limitless self‐renewal, governed by TERT expression and telomerase activation, is crucial for cancer progression. Thus, telomerase activation through the interplay of mutations ( TERT p Mut ) and epigenetic alterations in the TERT promoter may provide further insight into UBC behavior. Here, we investigated the combined effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 36 publications
11
54
1
Order By: Relevance
“…Our previous study performed on APL cell lines identified two distinct functional domains in hTERT promoter, one distal and one proximal, differentially methylated (Azouz et al , 2010). These results are in agreement with the recent identification of the TERT hypermethylation oncologic region, a 433‐bp genomic region located −159 to −591 bp upstream the TSS (Castelo‐Branco et al , 2016; Leao et al , 2019; Lee et al , 2019), as a potential biomarker in several cancers. This region is of major importance, because its methylation status correlates with hTERT expression.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study performed on APL cell lines identified two distinct functional domains in hTERT promoter, one distal and one proximal, differentially methylated (Azouz et al , 2010). These results are in agreement with the recent identification of the TERT hypermethylation oncologic region, a 433‐bp genomic region located −159 to −591 bp upstream the TSS (Castelo‐Branco et al , 2016; Leao et al , 2019; Lee et al , 2019), as a potential biomarker in several cancers. This region is of major importance, because its methylation status correlates with hTERT expression.…”
Section: Discussionsupporting
confidence: 91%
“…THOR hypermethylation has been found as an alternative telomerase-activating mechanism in cancer that can act independently or in conjunction with TERT promoter mutations, further supporting the utility of THOR hypermethylation as a prognostic biomarker (Lee et al, 2018). Other studies highlight that both THOR hypermethylation and TERT promoter mutations are common and coexist in bladder cancer, and while TERT promoter mutation behaves as an early event in bladder carcinogenesis, THOR hypermethylation seems associated with disease progression, with the combined genetic and epigenetic alterations of TERT bringing additional prognostic value in NMIBC (Leão et al, 2019). TERT promoter mutations per se emerged as a novel biomarker detected in up to 80% of bladder cancer, independently of stage or grade (Rachakonda et al, 2013;Allory et al, 2014;Hurst et al, 2014;Hosen et al, 2015).…”
Section: Introductionmentioning
confidence: 85%
“…THOR is an alternative telomerase-activating mechanism in cancer and can be a prognostic biomarker [78]. Directly related to BC, THOR hypermethylation and TERTp mutations are common and coexist in BC; THOR hypermethylation associates with disease progression, with the combined genetic and epigenetic alterations of TERT, bringing additional prognostic value in NMIBC [79].…”
Section: Tertp Mutations and Hypermethylationmentioning
confidence: 99%